Autoantibodies to recombinant canine proinsulin in canine diabetic patients. - Davison, L; Herrtage, M; Catchpole, B (2011)
OBJECTIVE: To determine whether dogs with spontaneously-occurring diabetes mellitus demonstrate serological reactivity to proinsulin. SAMPLE POPULATION: Serum samples were collected from 15 newly-diagnosed diabetic, 15 insulin-treated diabetic and 15 non-diabetic control dogs. PROCEDURES: Canine proinsulin was cloned into a prokaryotic expression vector to generate recombinant poly-histidine-tagged protein in Escherichia coli. A Western blotting assay was developed for detection of proinsulin autoantibodies in canine sera. RESULTS: Reactivity to canine proinsulin was detected in 3 of 15 control dogs, 8 of 15 newly-diagnosed diabetic dogs and 6 of 15 insulin-treated diabetic patients. Of these reactors, only 1 control dog, 1 newly-diagnosed diabetic dog and 3 insulin-treated diabetic dogs recognised porcine insulin by ELISA, suggesting that the remaining proinsulin reactors might have been recognising proinsulin-specific epitopes. CONCLUSIONS AND CLINICAL RELEVANCE: This study suggests that proinsulin autoantibodies are present in a proportion of diabetic dogs. Further work is required to refine the assay and clarify the significance of these autoantibodies.